Regional resilience in post-disaster recovery efforts of Merapi eruption based on local wisdom in Sleman Regency - Fitria Yusrifa; Agus Danugroho (Jurnal Sosiologi Dialektika, 2022)
Mount Merapi is located in two administrative regions, namely Central Java and Yogyakarta Special Region. Subsequent to the major eruption in 2010, the Sleman district government of Yogyakarta continued to formulate various policies related to post-disaster regional development. This study aims to explore regional development post-eruption of Merapi in Sleman, Yogyakarta, and formulate strategies that can be applied to the development of disaster-prone areas in Indonesia based on local wisdom. This research is qualitative research, which uses a literature review data collection method. The data were obtained and then processed by using CAQDAS (Computer-assisted Qualitative Data Analysis Software)-NVIVO 12 Plusâ„¢ application. The results of this study show that the existence of harmonious local wisdom among residents and the Javanese view of life triggered high optimism to rebuild areas affected by the eruption. Regional development strategies that are based on local wisdom are considered capable of overcoming post-disaster trauma and accelerating regional development. It also supported regional resilience goals that were needed to rebuild the affected areas. Based on the findings of this study, as areas with considerable potential and threat of disaster, Sleman and DIY can be role models for other regions to live in harmony with disasters.